THE EFFECT OF PROVIDING DIFFERENT FORAGES WITH THE SAME BASIC FEED ON THE APPEARANCE OF CLIRING CRICCAES (Grilus mitratus) - M. R., Subakat; Suasta, I M.; Sudiastra, I W. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study was to determine the effect different forage on the appearance of cliring crickets (Grilus mitratus) and was conducted for four weeks at the Teaching Farm of the Faculty of Animal Science, Udayana University, Bali. The research design used was a completely randomised design (CRD) consisting of 4 treatments and 5 replicates. Each replicate consisted of 30 crickets aged 10 days, resulting in 600 crickets with a body weight of ±3 mg. The four treatments were P1 (commercial feed + banana leaves), P2 (commercial feed + chicory), P3 (commercial feed + papaya leaves), and P4 (commercial feed + chicory and papaya leaves). The variables observed in this study included mortality, feed consumption, body weight gain, and feed conversion ratio (FCR). The data obtained were analysed using variance analysis, if there were differences (P<0.05) then the analysis was continued with Duncan's multiple range test. The results showed that feeding commercial feed added with chicory gave a significant difference (P<0.05) in the variables of mortality, consumption, body weight gain, and feed conversion ratio (FCR). Based on the results of the study, it can be concluded that feeding commercial feed with the addition of chicory can improve the appearance of cliring crickets (Grilus mitratus).